Synthesis and Bioactive Investigation of Amino Acids Fused 1,3,4-Oxadiazole Derivatives as Unnatural Amino Acids - Bisht, Ajay Singh; Juyal, Divya (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: In present study 1,3,4-oxadiazole was attempted to synthesize from nicotinic acid and further their amino acid derivates were formed. Amino acids play a significant role in biological system. Only 20 amino acids are naturally used, yet even little changes to these amino acids can produce an amazing diversity in terms of their chemical structure and function. Unnatural amino acids can be used to develop novel drugs, novel hormones, and novel enzymes. Materials and Methods: Derivatives were tried to synthesize from two methods, conventional as well as new microwave method in order to find out highest yielding method. Microwave method also referred to as "green chemistry" because it uses no external energy sources to produce any harmful fumes, gases, or heat. Results: “Method B” i.e., microwave used method found to be produce high yield. Amino acids which are fused to 1,3,4-oxadiazole were said to be unnatural amino acids. The compound(s) were analyzed using UV, IR and NMR spectral data. Synthesized compound(s) were experienced for in vitro free radical scavenging activity by DPPH and found to have promising activity. Conclusion: Synthesis of unnatural amino acids is an area for new research that has gained an attention now days. Study provides a facile route for preparation of Unnatural amino acids with derivatives and for its similar compound(s). The results could be a crucial study in the designing of novel therapeutic drugs in future.
Keywords: 1; 3; 4-oxadiazole; Unnatural amino acids; Microwave synthesis; Scavenging activity; Amino acids; DPPH